Iron isotope constraints on source and transport of sediment-derived dissolved Fe in the Weddell Sea region - Hung-An Tian; Mathijs van Manen; Zach B. Bunnell; Gert-Jan Reichart; Tim M. Conway; Rob Middag (Geochimica et Cosmochimica Acta, 2026)

Dissolved zinc and cadmium isotope systematics in the Amundsen and Weddell coastal Antarctic marginal seas - Hung-An Tian; Mathijs van Manen; Charlotte Eich; Jinyoung Jung; Willem H.v.d. Poll; Gert-Jan Reichart; Tim M. Conway; Rob Middag (Geochimica et Cosmochimica Acta, 2025)

Source and fate of atmospheric iron supplied to the subarctic North Pacific traced by stable iron isotope ratios - Minako Kurisu; Kohei Sakata; Jun Nishioka; Hajime Obata; Tim M. Conway; Hannah R. Hunt; Matthias Sieber; Katsuhiko Suzuki; Teruhiko Kashiwabara; Sayuri Kubo; Makoto Takada; Yoshio Takahashi (Geochimica et Cosmochimica Acta, 2024)

Microbially-mediated reductive dissolution of Fe-bearing minerals during freeze-thaw cycles - Jinwook Kim; Young Kyu Park; Tae-hee Koo; Jaewoo Jung; Insung Kang; Kitae Kim; Hanbeom Park; Kyu-Cheul Yoo; Brad E. Rosenheim; Tim M. Conway (Geochimica et Cosmochimica Acta, 2024)

A rapid procedure for isotopic purification of copper and nickel from seawater using an automated chromatography system - Xiaopeng Bian; Shun-Chung Yang; Robert J. Raad; Nicholas J. Hawco; Jude Sakowski; Kuo-Fang Huang; Kyeong Pil Kong; Tim M. Conway; Seth G. John (Analytica Chimica Acta, 2024)

Iron, Nickel, Copper, Zinc, and their stable isotopes along a salinity gradient in the Pearl River Estuary, southeastern China - Yaqing Ruan; Ruifeng Zhang; Shun-Chung Yang; Ziyuan Jiang; Sang Chen; Tim M. Conway; Kuo-Fang Huang; Edward A. Boyle; Meng Zhou; Seth G. John (Chemical Geology, 2024)

Biogeochemistry of iron in coastal Antarctica: isotopic insights for external sources and biological uptake in the Amundsen Sea polynyas - Hung-An Tian; Mathijs van Manen; Zach B. Bunnell; Jinyoung Jung; Sang Hoon Lee; Tae-Wan Kim; Gert-Jan Reichart; Tim M. Conway; Rob Middag (Geochimica et Cosmochimica Acta, 2023)

The biogeochemistry of zinc and cadmium in the Amundsen Sea, coastal Antarctica - Hung-An Tian; Mathijs van Manen; Flora Wille; Jinyoung Jung; SangHoon Lee; Tae-Wan Kim; Shigeru Aoki; Charlotte Eich; Corina P.D. Brussaard; Gert-Jan Reichart; Tim M. Conway; Rob Middag (Marine Chemistry, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)